Gesture Recognition for 3D Human Computer Interface: A Review (International Journal of Engineering and Computer Science, 2014)
In today’s world every individual is surrounded by smart technology. Everyone needs a technology that can interact and work. Research is going on to develop new methods of man-machine interfaces that are more user friendly. Touch based interaction has become a common method to operate mobile phones and tablet PCs. Another gesture recognition technology uses a camera that reads the movements of the human body and communicates the data to a computer that uses the gestures as input to control devices or applications. Gesture recognition enables humans to interface withthe machine (HMI) and interact naturally without any mechanical device i.e. without any physical contact. Thispaper presents a survey on different Gesture recognition ways currently in use and under research.